Independensi Kewenangan Jaksa Dalam Penuntutan Tindak Pidana Korupsi Menurut Undang-Undang Nomor 16 Tahun 2004 Tentang Kejaksaan Republik Indonesia - Royani, Ita (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2024)
The handling of corruption crimes is carried out by the Prosecutor's Office as a law enforcement agency, and the prosecutor, in addition to being a general prosecution officer, has a strong and planned legal foundation. Especially in the investigation as has been regulated in Article 30 (1) of Law No. 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia. Under article 2 of Act No. 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia, prosecutors are empowered to prosecute corruption offences independently without the assistance of any other party. The guarantees given by the law to prosecutors as part of the legal structure should result in a fair and human prosecution to maintain law and order and security.